2022
DOI: 10.1007/s10865-021-00267-1
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and multiple health domains: associations among emerging adults

Abstract: Emerging adults (18–25 years), particularly racially/ethnically diverse and sexual and gender minority populations, may experience loneliness following major life transitions. How loneliness relates to health and health disparities during this developmental period is not well understood. We examine associations of loneliness with physical (self-rated health), behavioral (alcohol/marijuana consequences; nicotine dependence), and health behavior outcomes (weekday and weekend sleep; trouble sleeping), and investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
(77 reference statements)
1
3
1
Order By: Relevance
“…The lack of a significant association between loneliness and substance co-use in our study marks a notable departure from findings reported in other regions [ 27 , 28 ]. This difference may be attributed to cultural variations in social relationships and coping strategies among Filipino adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of a significant association between loneliness and substance co-use in our study marks a notable departure from findings reported in other regions [ 27 , 28 ]. This difference may be attributed to cultural variations in social relationships and coping strategies among Filipino adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, loneliness predicted increases in sleep difficulties over time. The current study's results correspond to similar studies in which higher levels of loneliness were associated with poorer sleep quality in emerging adults during the COVID-19 pandemic [135]. According to Perez and colleagues (2022), the reasons for the relationship between loneliness and sleep difficulties may include those related to inflammation.…”
Section: Sleep Difficultiessupporting
confidence: 88%
“…Fourth, both sexual minority stress and intraminority gay community stress may impair the functioning of their relationships and result in loneliness directly [2]. Loneliness has been identified as a risk factor for physical health problems [15][16][17], depression and anxiety [16], suicidal ideation [18], sleep disturbance [17], cannabis use [17] and sexual risk behaviors [19,20], among sexual-minority individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Scrutinizing the psychometric evidence on the factor structure of the UCLA Loneliness Scale (Version 3), a bifactor structure (i.e., a general factor of loneliness with two method factors of positive wording and negative wording) has been supported (e.g., English version [37], Farsi version [38], Turkish version [39]). Moreover, some evidence shows that the UCLA Loneliness Scale (Version 3) has a unidimensional structure [17,18]. In brief, the full version of the UCLA Loneliness Scale (Version 3) can be viewed as having a unidimensional structure in relation to loneliness, but the unidimensional structure may be or may not be influenced by wording effects.…”
Section: Introductionmentioning
confidence: 99%